Indonesia - Investing in Indonesia's Education at the District Level : An Analysis of Regional Public Expenditure and Financial Management - World Bank (World Bank, 2012)
Since the implementation of decentralization in 2001, district governments have been getting increased responsibilities to provide education services to the citizen. Basic and secondary education management authority has been fully transferred from the central to the provincial and district government. District education expenditure has grown rapidly both in terms of level and as a share of national education expenditure. The amount of district education expenditure has increased from Rp. 26 trillion in 2001 to 52 trillion in 2006 and they constitute 50 percent of the total national education public expenditures in 2006. This review of district education expenditures is one of the outputs of a larger set of analytical and design activities that will prepare the ground for System Improvement through Sector Wide Approaches (SISWA) Program in basic education. In 2006, 56 percent of education expenditure was spent at the sub-national level. District governments are the main spenders, accounting for 51 percent of total spending, while provincial governments account for just over 5 percent. These shares of total education spending demonstrate the trend in education service delivery, with district government shares being relatively high compared with the central government. District education expenditure has increased since decentralization. However, the budget share of district education spending has been decreasing. This decreasing trend, particularly since 2005, may have been influenced by BOS (school operational assistance) transfers from the central government. Net enrollment rates (NERs) at the primary school level in most of the visited districts are close to universal, except in some remote districts in Papua. Districts with high NERs at the primary level also tend to have high NERs at the junior secondary level. Differences in NERs at the primary and junior secondary levels are more significant in kabupaten (district) than kota (city) areas. This situation suggests a higher transition rate from primary to secondary schools in urban than rural districts.